Smart management services for high-rise apartments in Beijing, China. Issue 5 (3rd September 2022) - Tong, Xiao Wen; Lee, Li Na; Kim, Mi Jeong
ABSTRACT: High-rise apartments are one representative form in the era of urbanization. However, the management of the high-rise apartment is not easy because of large household densities and the complex structures. Advanced technologies have permeated our daily lives and management services are becoming more intelligent. The aim of this study is to explore the smart management service model of high-rise apartments by investigating the current state of management services and residents' consciousness of it, as well as to identify necessary management services. A survey was conducted in two apartment complexes with a focus on the actual users' demands and preferences. The results show that the characteristics of the common space would be decided by considering residents' diverse needs for these common spaces. Further, residents of high-rise apartments lack awareness and experience of technologies for smart management. This suggests that smart management services should be developed in consideration of the perspectives of the residents to satisfy their psychological and safety needs. Virtual social spaces would be provided to create a sense of neighborhood among the residents. With a human-centered approach, this study would be a basis for the development of smart management services supporting the quality of residential life in high-rise apartments.